IMPROVING ARABIC LANGUAGE LEARNING BASED ON HIGHER ORDER THINKING SKILLS (HOTS) IN EXCELLENT SENIOR HIGH SCHOOL - Mokhammad Miftakhul Huda; Pandi Rais (LP2M UIN KH.Achmad Siddiq Jember, 2021)
Good Arabic learning cannot be separated from the method applied. The curriculum used at MAUDU has already applied K-13, but in fact many some teachers use the classical model. Therefore, a teaching model is necessary that can bring students not only able to answer questions, but also can understand the lessons much better. They can apply the material in their daily lives, analyze and evaluate what has/have been done. This model is known as HOTS (High Order Thinking Skills). This study tries to explain the HOTS system and its relation to Arabic literacy and to innovate the development of HOTS-based materials towards innovative learning. In this study, a descriptive approach, an analytical approach, and a critical approach were used. The results achieved in this study are the innovation of developing HOTS-based Arabic learning which includes several stages, they are basic competency analysis (KD), indicator analysis, student characteristics analysis, formulating learning objectives, material analysis, developing strategies, and learning activities, developing learning tools, developing assessments, linking the principles of HOTS (High Order Thinking Skills), and Revising all aspects and steps of learning development. Pembelajaran Bahasa Arab yang baik tidak terlepas dari metode yang digunakan. Kurukulum pembelajaran yang digunakan di MAUDU sudah menggunakan K-13, akan tetapi dalam pelaksanaannya banyak yang menggunakan model klasik. Karena itu diperlukan model pengajaran yang dapat membawa siswa tidak hanya sekedar dapat menjawab pertanyaan, tetapi siswa dapat memahami dengan lebih baik, menerapkan materi dalam kesehariannnya, juga dapat menganalisis dan mengevaluasi apa yang telah dikerjakan. Model tersebut dikenal dengan HOTS (High Order Thinking Skills). Penelitian ini berusaha untuk menjelaskan system HOTS dan kaitannya dengan literasi Bahasa Arab dan membuat inovasi pengembangan materi berbasis HOTS menuju pembelajaran yang inovatif. Dalam penelitian ini, digunakan pendekatan deskriptif, pendekatan analisis, dan pendekatan kritis. Hasil yang dicapai dalam penelitian ini adalah Inovasi pengembangan pembelajaran bahasa Arab berbasis HOTS yang meliputi beberapa tahapan, yaitu analisis kompetensi dasar (KD), analisis indikator, analisis karakteristik peserta didik, merumuskan tujuan pembelajaran, analisis materi, mengembangkan strategi, dan kegiatan pembelajaran, mengembangkan perangkat pembelajaran, mengembangkan penilaian, mengkaitkan prinsip HOTS (High Order Thinking Skills), dan Merevisi semua aspek dan langkah pengembangan pembelajaran